Dance fitness fitness dance - latin, funk and dance group exercise - Aagaard, Marina
Dance fitness - fitness dance, latin, funk and dance group exercise is an essential guide to creating dance classes for fun and fitness. Dance fitness is a general description covering many dance styles; common to all of them is a focus on dancing and having fun, while getting an excellent cardiovascular and motor skill workout. The book covers all the basic principles of dance fitness and gives numerous tips for increasing motivation and results via improved class design, dance move selection and methodology. The book contains more than 120 dance moves with step-by-step explanations illustrated by over 290 photos. For each dance move there are even more suggestions for variations at all levels. Dance fitness - fitness dance, latin, funk and dance group exercise is a book for group exercise instructors, dance and dance fitness instructors, e.g. Zumba, Batuka, Groove a.o., and sports study students